Inhibition of AHL-mediated quorum sensing to control biofilm thickness in microbial fuel cell by using Rhodococcus sp. BH4 - Taskan, Banu; Taskan, Ergin (Pergamon-Elsevier Science Ltd, 2021)
Anode biofilm thickness is a key point for high and sustainable power generation in microbial fuel cells (MFCs). Over time, the formation of a thicker biofilm on anode electrode hinders the power generation performance of MFC by causing a longer electron transfer path and the accumulation of undesirable components in anode biofilm. To overcome these limitations, we used a novel strategy named quorum quenching (QQ) for the first time in order to control the biofilm thickness on the anode surface by inactivation of signal molecules among microorganisms. For this purpose, the isolated QQ bacteria (Rhodococcus sp. BH4) were immobilized into alginate beads (20, 40, and 80 mg/10 ml sodium alginate) and added to the anode chamber of MFCs. The MFC exhibited the best electrochemical activity (1924 mW m(-2)) with a biofilm thickness of 26 mu m at 40 mg Rhodococcus sp. BH4/10 ml sodium alginate. The inhibition of signal molecules in anode chamber reduced the production of extracellular polymeric substance (EPS) by preventing microbial communication amonganode microorganisms. Microscopic observations revealed that anode biofilm thickness and the abundance of dead bacteria significantly decreased with an increase in Rhodococcus sp. BH4 concentration in MFCs. Microbiome diversity showed an apparent difference among the microbial community structures of anode biofilms in MFCs containing vacant and Rhodococcus sp. BH4 beads. The data revealed that the QQ strategy is an efficient application for improving MFC performance and may shed light on future studies.
Keywords: Quorum quenching (QQ); Biofilm thickness; Microbial fuel cell (MFC); Electricity generation; Microbial community composition